Case of the Development of a Biomedical Device Innovation Project of a Mexican Public University to Face COVID-19 - Roberto, Vega-González Luis; Sánchez, Pérez Celia A. (Archives of Business Research, 2022)
Through the case study method, in this article, the activities of an innovation project carried out by the Biomedical Devices group of the Institute of Applied Sciences and Technology of the National Autonomous University of México (UNAM) to face Covid-19 pandemic are presented. A notable result is that the drastic reduction of university development times required to deliver results to the health sector in the form of technological products to face the disaster situation is observed. However, it is also noted that some government authorities in the field of intellectual property and health permits act as barriers that make it difficult to reach the innovation frontier because the time required to obtain governmental authorizations. This situation made it difficult to reach the moment of launching the technological product to society. It is concluded that the joint reaction time of the different innovation actors is one of the main variables or dimensions that must be reduced through emergency policies and actions that must be planned, based on the organizational and individual learning that occurs in contingent situations.